Keynote Speech at the International Economic Forum of the Americas, Montreal, Canada, June 11, 2013 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group discusses the role of private sector as being essential for ending poverty by 2030, and for building shared prosperity so that the bottom 40 percent of the population shares in economic growth. He stresses the need to create a favorable environment in which it's easier to start a formal business with improved regulation and technology. He mentions that many leaders in the developing world are actively looking for ways to work more closely with private sector. He speaks about the need of Canadians and other international firms to invest in the developing world. He expresses the keen interest of World Bank to partner in developing countries and asks the government of Canada to help bend the arc of history and banish extreme poverty from this earth.